PENINGKATAN KEMAMPUAN BERBAHASA ANAK MELALUI METODE BERCERITA DENGAN MENGGUNAKAN MEDIA GAMBAR - Malwa, Rosyidah Umpu (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2016)
This study aims to determine improvements in language skills of children through storytelling using media images in group B TK Fajar Insan Palembang. Subjects in this study were children in group B TK Fajar Insan Palembang in the academic year 2015-2016, amounting to as many as four children, has two daughters and two sons. The method used is classroom action research, the process of the implementation of this action research is collaborative and participatory between principals, teachers, children and involved in the learning process. The results showed that the method of telling stories using media images can improve a child's language ability. It is shown from the results of the analysis showed that the average child's language ability Fajar Insan TK Group B in the first cycle was 2.95 and in the second cycle was 3.8.